Konstruksi Pasangan Calon Dalam Pilgub Jateng 2008 oleh Media Massa (Kasus Pemberitaan Jawa Pos Radar Semarang dan Suara Merdeka) - Yustitia, Senja (Universitas Semarang, 2009)
The research samples are news about the candidates in Jawa Pos Radar Semarang and Suara Merdeka daily newspaper page one and special rubric on March 26 - June 22, 2008. The result of this research shows that Jawa Pos Radar Semarang tried to be responsive with political issues and give favorable constructs to Agus Soeyitno-Kholiq Arif, Bibit Waluyo-Rustriningsih dan HM.Tamzil-Rozaq Rais. On the other hand, they give unfavorable constructs to Bambang Sadono-M. Adnan and Sukawi Sutarip-Sudharto. Suara Merdeka give favorable constructs to Bambang Sadono-M. Adnan; Bibit Waluyo-Rustriningsibd and HM. Tamzil-Rozaq Rais but give unfavorable constructs to Agus Soeyitno-Kholiq Arif and SukawiSutarip-Sudharto.